On Behavior of Sampled Signal when Value of Sampling Period Tends to Zero and Analog-to-Digital Conversion in Microwave Photonic Systems - Andrzej Borys (International Journal of Electronics and Telecommunications)
In this paper, we compare behaviors of two possible descriptions of the sampled signal in the case when the sampling period tends to zero, but remains all the time greater than zero. Note that this is the case we are dealing with in analog-to-digital conversion in microwave photonic systems. From this comparison, it follows that the description with the weighted step function is superior to the description with the weighted Dirac comb. A couple of useful comments and remarks associated with the results presented are also provided in the context of microwave photonic systems.